SILENCE: Arts Administration in the Time of COVID-19 - Raczycki, Scarlett (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
This piece identifies some of the unique challenges of the COVID-19 pandemic for non-profit arts administration. It profiles Silence, Guelph, a small music venue, art gallery and community space, and how we have experienced the pandemic and continue to learn from and grow through the challenges it presents.